2004
DOI: 10.1097/00002030-200403050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to loss of HIV-specific cytotoxic T lymphocyte activity

Abstract: Most HIV-infected individuals retain CD8 anti-HIV CTL with in vitro proliferative potential, even when antigen is limited. Those who lose HIV-specific CTL responses generally show past or current evidence of severe disease progression or activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…In the past decade, the correlation between CTL responses and immune control of HIV-1 infection has been extensively explored and controversial results have been reported[ 5 , 8 , 13 , 28 , 39 - 42 ]. A recent study has demonstrated that CTL responses to different HIV proteins have discordant associations with plasma viral load, which results in effective CTL responses without a demonstrable biological impact in chronic HIV infection[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the correlation between CTL responses and immune control of HIV-1 infection has been extensively explored and controversial results have been reported[ 5 , 8 , 13 , 28 , 39 - 42 ]. A recent study has demonstrated that CTL responses to different HIV proteins have discordant associations with plasma viral load, which results in effective CTL responses without a demonstrable biological impact in chronic HIV infection[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infects CD4+ T cells in the gut as early as a few weeks after infection, resulting in almost complete loss of this cell population [12–14]. Loss of mucosal CD4+ T-helper cells consequently results in a loss of function of both B cells and CD8+ T cells [15]. In HIV patients, CD4+ T cell depletion results in increased susceptibility to bacteremia caused by intestinal pathogens (mostly Salmonella , but also Shigella and Campylobacter ) [1618].…”
Section: Orchestrating the Gut Mucosal Barrier: An Emerging Role For mentioning
confidence: 99%
“…In the past decade, the correlation between T cell responses and immune control of HIV‐1 infection has been explored extensively, and some controversial results have been reported . Some previous studies have shown an inverse correlation between the magnitude and frequency of HIV‐specific CD8 + T cells and plasma VL , whereas such correlations were not observed in other studies .…”
Section: Discussionmentioning
confidence: 97%